Description of Haploblepharus kistnasamyi, a new catshark (Chondrichthyes: Scyliorhinidae) from South Africa - Human, Brett A.; Compagno, Leonard J.v. (Zootaxa, 2006)
A new species of catshark, Haploblepharus kistnasamyi sp. nov. (Class Chondrichthyes, Order Carcharhiniformes, Family Scyliorhinidae) is described from kwaZulu-Natal, South Africa. The type series includes the holotype, RUSI 39835, and two paratypes, RUSI 6075 and RUSI 6077. This species was previously recognised as a variant of H. edwardsii (Schinz 1822), which occurs along the southern coast of South Africa. The colour pattern of H. kistnasamyi is superficially similar to H. edwardsii although distinct; however H. kistnasamyi is distinguished from all other Haploblepharus in having a stockier build compared to its congeners, a less depressed head and trunk, and a compressed caudal peduncle.